2020
DOI: 10.1177/1756286420935697
|View full text |Cite
|
Sign up to set email alerts
|

C3, C5a and anti-acetylcholine receptor antibody as severity biomarkers in myasthenia gravis

Abstract: Background: Although the pathogenesis of myasthenia gravis (MG) is well known, prognostic markers are not yet available. We assessed the utility of anti-acetylcholine receptor (AChR) antibody (AChR-ab) titer and concentration of C3, C4, and C5a as potential severity biomarkers in MG. Methods: Levels of C3, C4, C5a, and AChR-ab were measured in 60 AChR-ab-positive patients with MG. Their relationship with clinical severity was analyzed using the activities of daily living (ADL) and MG composite (MGC) scales. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Other studies have also shown a correlation of MuSK-AB-titer and MG severity in general [ 20 ]. Aguirre et al [ 21 ] demonstrated similar results; they found a relation between AchR-AB titers and disease severity in the first 5 years of MG as well as they detected complement factor C5a significantly elevated in severe disease courses as a non-specific marker. Up to our knowledge, only a few studies, especially case reports , exist that repetitively measured antibody titers during disease course.…”
Section: Discussionmentioning
confidence: 67%
“…Other studies have also shown a correlation of MuSK-AB-titer and MG severity in general [ 20 ]. Aguirre et al [ 21 ] demonstrated similar results; they found a relation between AchR-AB titers and disease severity in the first 5 years of MG as well as they detected complement factor C5a significantly elevated in severe disease courses as a non-specific marker. Up to our knowledge, only a few studies, especially case reports , exist that repetitively measured antibody titers during disease course.…”
Section: Discussionmentioning
confidence: 67%
“…After treatment, the indices returned to their original baseline levels. Interestingly, C5a levels were positively correlated with MG severity according to the activities of daily living (ADL) scale (32). Components of the complement system can be considered as markers for diagnosis and disease, as well as targets for therapy.…”
Section: The Complement System In Mgmentioning
confidence: 99%
“…The pathogenesis of MG is extremely complex and its occurrence is the result of the interaction between the genetic susceptibility of the host, the influence of environmental infectious factors, and the body's own immune response. AChR antibody [10][11], other major pathogenic autoantibodies, and THymus CD4+ T lymphocytes [12] play an important role in MG pathogenesis. Although the mechanism of MG relapse may be related to the β 2 adrenergic receptor, this mechanism is still unclear and rarely studied [13].…”
Section: Monofactorial Analysismentioning
confidence: 99%